Longitudinal changes in brain glucose metabolism, astrocyte biomarkers and behavior in an APP/PS1 rat model. (20th December 2022) - da Rocha, Andreia Silva; Machado, Luiza Santos; Soares, Carolina; Ferreira, Pamela C.L.; Bellaver, Bruna; Kunach, Peter; Rosa‐Neto, Pedro; Green, Kim N; Zimmer, Eduardo R.; ,
Abstract: Background: Imaging and fluid biomarkers have helped to reconceptualize Alzheimer's Disease (AD) as a continuum. However, the biological interpretation of each AD biomarker remains under investigation. In this context, animal models that mimic the AD dynamic biomarkers cascade model present high translational value and can be used to refine our interpretation of biomarker findings. In light of this, we longitudinally evaluated [ 18 F]FDG‐PET imaging, cerebrospinal fluid (CSF) glial and immune biomarkers, and behavior in the TgF344‐AD rat, a model harboring human APP/PS1 mutations. Methods: TgF344‐AD rats and wild‐type littermates were longitudinally evaluated at 3, 6, 9, and 12 months of age. Rats underwent [ 18 F]FDG‐microPET scans, behavioral tasks (Y‐maze and novel objective recognition) and CSF samplings. The [ 18 F]FDG SUVr was calculated with pons as the reference region. CSF glial and immune markers were measured by multiplex ELISA. A cross‐sectional cohort was used to measure cortical glutamate uptake (ex‐vivo slices) at the same time points. Further examination of astrocyte proteins immunocontent was conducted at 9 months of age. Results: At 3, 6 and 12 months, no changes in [ 18 F]FDG metabolism were found. At 9 months of age, we identified a significant cortical hypermetabolism in the TgF344‐AD and a decline in alternance during the Y‐maze task. CSF GFAP levels were elevated at 6 and 9 months of age, while CSF S100B was decreased at 9 months of age. Additionally, the cortical and hippocampal glutamate uptake and GFAP cortical immunocontent were increased at 9 and 12 months of age. The recognition memory and CSF inflammatory markers (sTREM2, IL‐6, TNF‐α, IL‐10) were not altered in any of the ages evaluated. Conclusion: Our results suggest that the TgF344‐AD rat model is suitable for studying astrocytic adaptations during early stages of amyloidosis in the rat brain. These adaptations include cortical glucose hypermetabolism, fluid biomarker evidence of reactive astrogliosis, and spatial memory impairment with concurrent abnormalities in astrocyte glutamate uptake in the cortex and hippocampus. Due to the critical role of astrocytes in brain glucose handling, our findings suggest that astrocyte reactivity could be driving glucose hypermetabolism and memory impairment early in the disease course.